Pengaruh Penggunaan Buah Alpukat dan Virgin Coconut Oil (VCO) Terhadap Perawatan Rambut Rontok - Syannaz Rizka Usman; Yuliana Yuliana (JURNAL PENDIDIKAN DAN KELUARGA, 2020)
Excessive hair loss will cause baldness. It can will influence someone’s confidence. that is why, hair loss treatment is needed to be done. One of them is by using avocados and VCO. They have good function to stimulate hair growth and make them healthier. This study aims to analyze the effect of avocados and VCO toward hair loss treatment. The research was done by observing the mount of hair loss everyday. this study was conducted with a quasi-experimental method with a quasi exsperiment to explain the influence of using avocados and VCO on the treatment of hair loss. The research subjects were a collection of women who lived in the Parak Laweh area of ​​Lubuk Begalung subdistrict which improved hair loss at the level of 40-100 strands per day. The sample in this study amounted to 12 people used by the technique of taking documentation and interviews. This study consisted of 4 different groups, namely the control group (X0), experimental group 1 (X1), experimental group 2 (X2), and experimental group 3 (X3).The data gathered is primary data. It is directly taken from samples that fill in the research format provided. Data analysis using analysis of variance (anava) and continued with Duncan test, the results of this study show a significant difference in the indicator of the amount of hair detached from the scalp with the number of strands of hair falling after treatment in the control group (X0) (80.50), experimental group 1 (X1) (60.50), experimental group 2 (X2) (58.83) and experimental group 3 (X3) (58.67). So it can be said that for the indicator of the amount of hair loss in the experimental group did not show a statistically significant difference, but there was a significant difference in the treatment of hair loss in the control group. Keywords: hair loss, avocados, VCO